Dramatyczne prologi w diegematycznych dialogach Platona - Głodowska, Anna (Collectanea Philologica, 2023)
In Plato’s diegetic dialogues, as well as in dramatic works, you can ﬁnd a distinctive feature, an autonomous part opening the work, which is usually called “a prologue”. This term is taken from an ancient Greek drama and means in literal translation “before the content”. In dramatic scenes, which precede the main narrative part of Plato’s dialogues, one of the characters is so interested in the discussion held by Socrates in more or less distant past, that he asks the discussion participant or the person who has some knowledge about it to relate him the debate. The aim of this analysis are the prologues in Protagoras, Phaedo, Symposium, Euthydemus and Theaetetus to answer the question what function in Plato’s dialogue structure they play.